(untitled) (Research, Society and Development, 2022)
During the COVID-19 pandemic in Brazil, the Pan American Health Organization (PAHO) reported an increase in maternal deaths in the country, between January and April 2021. In the period, the FioCruz Organization reported that the fatality rate of COVID-19 19 was higher in pregnant and postpartum women compared to the general population of the country. In an attempt to delay the spread of the virus among pregnant women, in May/2021, Law 14.151/2 was published, providing for the compulsory removal of pregnant women from their in-person workplace, preserving their remuneration in full. In this way, several Brazilian companies were impacted. Objective: to understand why Law 14.151/2 was necessary in the country, as well as what were the impacts on companies in Serra Catarinense. Methodology: A literature review was carried out, defining inclusion and exclusion criteria for the articles to be analyzed, such as keywords, search fields, document types, language and year of publication. An explanatory, descriptive and exploratory research was carried out, aiming to understand what were the consequences generated in companies in the Serra Catarinense. Results and Discussion: The Law seeks to protect pregnant women, as they have a greater potential for illness due to the intense physiological changes caused in the pregnancy period, however, companies in Serra Catarinense suffered a negative impact, mainly financially. Conclusion: The creation of the law was fundamental, however, it generated several consequences for the companies of Serra Catarinense, and it is necessary to carry out more studies, with a greater number of companies, in order to analyze other outcomes generated by the Law.